Efektivitas edukasi berbasis web terhadap tingkat kecemasan pasien: A systematic review - Monica, Rica; Awaludin, Sidik (Holistik Jurnal Kesehatan, 2025)
Background: Anxiety is one of the psychological problems often experienced by patients with various medical conditions. Web-based education has developed as an intervention method to reduce patient anxiety. However, the effectiveness of this method still needs to be studied further. Purpose: To evaluate the effectiveness of web-based education on patient anxiety levels. Method: Systematic review research with Preferential Reporting Items for Systematic Reviews And Meta Analysis (PRISMA) reference to search for articles related to web-based educational interventions and their impact on patient anxiety. Article search from databases such as PubMed with keywords namely Web-based education AND patient anxiety, telehealth AND anxiety management, and digital health intervention AND psychological distress. Results: Studies have shown that web-based education can significantly reduce patient anxiety levels. Factors supporting the effectiveness of this intervention include interactive modules, online support, and flexibility of access. However, there are barriers such as limited digital access for some patient groups. Conclusion: Web-based education has been shown to be effective in reducing patient anxiety across a range of medical conditions. Further implementation is needed to improve patient engagement and the quality of online educational content.   Keywords: Anxiety; Education; Web-Based.   Pendahuluan: Kecemasan merupakan salah satu masalah psikologis yang sering dialami oleh pasien dengan berbagai kondisi medis. Edukasi berbasis web telah berkembang sebagai metode intervensi untuk mengurangi kecemasan pasien. Namun, efektivitas metode ini masih perlu dikaji lebih lanjut. Tujuan: Untuk mengevaluasi efektivitas edukasi berbasis web terhadap tingkat kecemasan pasien. Metode: Penelitian systematic review dengan acuan Preferential Reporting Items for Systematic Reviews And Meta Analysis (PRISMA) untuk mencari artikel terkait intervensi edukasi berbasis web dan dampaknya terhadap kecemasan pasien. Pencarian artikel dari database berupa PubMed dengan kata kunci yaitu Web-based education AND patient anxiety, telehealth AND anxiety management, dan digital health intervention AND psychological distress. Hasil: Studi menunjukkan bahwa edukasi berbasis web dapat menurunkan tingkat kecemasan pasien secara signifikan. Faktor-faktor yang mendukung efektivitas intervensi ini meliputi modul interaktif, dukungan daring, dan fleksibilitas akses. Namun, terdapat hambatan seperti keterbatasan akses digital bagi beberapa kelompok pasien. Simpulan: Edukasi berbasis web terbukti efektif dalam mengurangi kecemasan pasien di berbagai kondisi medis. Implementasi lebih lanjut diperlukan untuk meningkatkan keterlibatan pasien dan kualitas konten edukasi daring.   Kata Kunci: Edukasi; Berbasis Web; Kecemasan.